How do we know that physical spacetime in cosmology is smooth and 4-dimensional? - Król, Jerzy (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2017)
Even though the description of the universe in cosmology is known to be given by a smooth 4-dimensional Lorentz manifold for energies below Planck scale, one still can ask about the origins of this phenomenon. In this paper we show that mathematics used for description of quantum systems at micro scale determines smoothness of spacetime at large cosmological scales and indicates the dimension 4 as the only possible dimension for spacetime.